2022
DOI: 10.7554/elife.84060
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension in female mice by early, transient exposure to adult female olfactory cues

Abstract: Several previous lines of research have suggested, indirectly, that mouse lifespan is particularly susceptible to endocrine or nutritional signals in the first few weeks of life, as tested by manipulations of litter size, growth hormone levels, or mutations with effects specifically on early-life growth rate. The pace of early development in mice can also be influenced by exposure of nursing and weanling mice to olfactory cues. In particular, odors of same-sex adult mice can in some circumstances delay maturat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
4
2
Order By: Relevance
“…Such desensitization was another reason that these authors cautioned against drawing conclusions from their negative results. A recently published study on laboratory mice found no evidence that exposure to adult urine affected the growth of either sex 44 , in contrast to a previous study that reported that exposure to the urine of adult virgin females reduced female growth 45 . Interestingly, this recent study found that exposing female mice to the urine of adult females (but not males) increased their longevity (8% in median lifespan), though exposing males to adult urine from either sex had no such effects 44 .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Such desensitization was another reason that these authors cautioned against drawing conclusions from their negative results. A recently published study on laboratory mice found no evidence that exposure to adult urine affected the growth of either sex 44 , in contrast to a previous study that reported that exposure to the urine of adult virgin females reduced female growth 45 . Interestingly, this recent study found that exposing female mice to the urine of adult females (but not males) increased their longevity (8% in median lifespan), though exposing males to adult urine from either sex had no such effects 44 .…”
Section: Discussioncontrasting
confidence: 61%
“…A recently published study on laboratory mice found no evidence that exposure to adult urine affected the growth of either sex 44 , in contrast to a previous study that reported that exposure to the urine of adult virgin females reduced female growth 45 . Interestingly, this recent study found that exposing female mice to the urine of adult females (but not males) increased their longevity (8% in median lifespan), though exposing males to adult urine from either sex had no such effects 44 . Taken together, these studies indicate that exposure to the urine of conspecifics have surprising effects on growth, sexual maturation and even longevity, however, it is unclear how to explain the discrepancies among the studies.…”
Section: Discussioncontrasting
confidence: 61%
“…Like the vasculature, the sympathetic nervous system impacts the function of many peripheral organs, and synapse function plays a critical role in the function and the maintenance of the CNS. Hints of such an association have come from genetics studies of worms (Apfeld and Kenyon, 1999; Li et al, 2016), flies (Libert et al, 2007) and laboratory rodents (Garratt et al, 2022; Zullo et al, 2019). It is possible that synapse function accounts for the association of computer gaming with ΔAge.…”
Section: Resultsmentioning
confidence: 99%
“…This is accompanied by lifespan extension and reduced accumulation of toxic polyglutamine expansions ( De-Souza et al, 2022a preprint). In parallel, another group observed that exposure to a specific odour (urine) extends the lifespan of female mice ( Garratt et al, 2022 preprint). Identifying strategies for keeping stress responses functional as we age, particularly in the brain, is a promising area of study that may have an impact on age-related disorders.…”
Section: Discoveriesmentioning
confidence: 95%